Association of interferon regulatory factor 8 dysregulation with dry eye in Sjögren’s syndrome - Jiao Wang; Guang-Hong Chu; Zi-Huan Wang; Xiao-Yu Cai; Si-Yuan Shi; Qi-Ping Qing; Qi Zhang (International Journal of Ophthalmology, 2025)
AIM: To investigate the expression of interferon regulatory factors (IRFs) in peripheral blood mononuclear cells (PBMCs) of patients with Sjögren's syndrome-related dry eye (SSDE) and to explore their correlation with clinical features, dendritic cell activation, and serological indicators. METHODS: A total of 53 SSDE patients and 62 non-Sjögren's syndrome dry eye (NSSDE) patients were enrolled. Demographic and clinical data were collected, and comprehensive ophthalmic examinations were performed, including the ocular surface disease index (OSDI) questionnaires, Schirmer I test (SIT), tear break-up time (TBUT), corneal fluorescein staining score (CFS), and in vivo confocal microscopy (IVCM). PBMCs were isolated, and IRFs expression levels were analyzed using Western blotting (WB) and quantitative real-time polymerase chain reaction (qRT-PCR). Serological indicators, including antinuclear antibodies (ANA) and anti-Ro60, anti-Ro52, and anti-La autoantibodies, were detected. Statistical analyses evaluated correlations between IRFs expression and clinical parameters. RESULTS: Compared to NSSDE, the relative mRNA and protein expression of the IRF-8 was significantly upregulated in patients with SSDE (P<0.001), whereas no significant differences were observed in IRF-1, IRF-3, IRF-5, and IRF-7 (P=0.12, P=0.10, P=0.66, P=0.96). Correlation analysis revealed that IRF-8 expression was positively associated with CFS and OSDI scores (r=0.57, r=0.38, both P<0.05). Moreover, IRF-8 expression correlated with corneal dendritic cell (DC) density and size, and the number of dendrites (r=0.43, r=0.40, r=0.65, all P<0.05). IRF-8 expression was significantly elevated in patients positive for anti-Ro60, anti-Ro52 and anti-La autoantibodies (P<0.05). CONCLUSION: In SSDE, IRF-8 is upregulated and associated with clinical features, DC activation, and serological indicators. These findings suggest that IRF-8 plays a critical role in SSDE pathogenesis and may serve as a potential therapeutic target for diagnosis and treatment.